Sundanesse Sound Interference Into English In The Text Of Being The Moderator - Sri Rahayu (STISIP Widyapuri Mandiri Sukabumi, 2024)
In Indonesia, English pronunciation for students is very difficult, because the differences between Indonesian and other regional languages do not exist in English, and some vocal and consonant sounds are very different. There are many difficulties for regional students who have to generalise with English. Because it must be adjusted to Indonesian first. Various supporting factors in the delivery of English are very important, both in the environment, and family. The role of a mother as a teacher in daily life is very instrumental. Structural differences can cause errors in learning a foreign language, learners are usually distracted by the first language or mother tongue, so that it can cause sound interference to the language being studied.